(3GdJhVjM aj Md ZhGeV GdJfbjMs - (3UOQ GdTQjYI GdKGfj, YHjO Gddg Hf eSYhO Hf JGL GdTQjYI eMehO GdeMHhHj, J (B747(3g`s
(3ChdgG (B:s
(3edc edhc GdESdGe GdeTQa HGdLgGO aj SHjd Gddg hRjGQI HjJg GdMQGe GdPj JVYVY HUOeJg eHGfj GdgQeGf hGgJR HMSf TYGFQg GdeTGYQ SejJ gPG GdcJGH HGdJhVjM aj Md ZhGeV GdJfbjMs
(3BNQgG (B:s
(3hCeG Mbhb GdYHGO cEJdGa eGd GdeSde aMceg Mce CNhjg aj Cfg eQNU HGdedLF hEf UHQ UGQ TgjOG Ch GdeQGO HCNhjg (B( ) (3dG JSbW jMJed GdSbhW (B( ) (3dcfgG de JSbW (B( ) (3hge Mb Gddg JYGdi hjLH GdVeGf dhLhO GdYUeI hGddg hdj GdYUeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 197s
(3eYLe GdeDdajf (B2 / 355s
(3cTa GdXfhf (B1 / 496s
(3GdahGFO GdHgjI (B109s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs